Розроблення пристроїв на постійних магнітах для очищення вибоїв свердловин від металу при бурінні - Романишин, Л.І.; Романишин, Т.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The factors which influence power and magnetic characteristics of magnetic systems are in
the focus of attention. The given results of theoretical and experimental research has become the
basis for streamline system construction of magnetic tools for bottom hole cleaning on the base of
highly powered magnets.